A comparison of non-magnetic and magnetic beads for measuring IgG antibodies against Plasmodium vivax antigens in a multiplexed bead-based assay using Luminex technology (Bio-Plex 200 or MAGPIX). - Ramin Mazhari; Jessica Brewster; Rich Fong; Caitlin Bourke; Zoe S J Liu; Eizo Takashima; Takafumi Tsuboi; Wai-Hong Tham; Matthias Harbers; Chetan Chitnis; Julie Healer; Maria Ome-Kaius; et al. (PLoS ONE)
Multiplexed bead-based assays that use Luminex® xMAP® technology have become popular for measuring antibodies against proteins of interest in many fields, including malaria and more recently SARS-CoV-2/COVID-19. There are currently two formats that are widely used: non-magnetic beads or magnetic beads. Data are lacking regarding the comparability of results obtained using these two types of beads, and for assays run on different instruments. Whilst non-magnetic beads can only be run on flow-based instruments (such as the Luminex® 100/200™ or Bio-Plex® 200), magnetic beads can be run on both these and the newer MAGPIX® instruments. In this study we utilized a panel of purified recombinant Plasmodium vivax proteins and samples from malaria-endemic areas to measure P. vivax-specific IgG responses using different combinations of beads and instruments. We directly compared: i) non-magnetic versus magnetic beads run on a Bio-Plex® 200, ii) magnetic beads run on the Bio-Plex® 200 versus MAGPIX® and iii) non-magnetic beads run on a Bio-Plex® 200 versus magnetic beads run on the MAGPIX®. We also performed an external comparison of our optimized assay. We observed that IgG antibody responses, measured against our panel of P. vivax proteins, were moderately-strongly correlated in all three of our comparisons (pearson r>0.5 for 18/19 proteins), however higher amounts of protein were required for coupling to magnetic beads. Our external comparison indicated that results generated in different laboratories using the same coupled beads are also highly comparable (pearson r>0.7), particularly if a reference standard curve is used.